2010
DOI: 10.1111/j.1365-2133.2010.09696.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response towards the amino-terminus of desmoglein 1 prevails across different activity stages in nonendemic pemphigus foliaceus

Abstract: Most of the anti-Dsg1 antibodies in nonendemic PF bind to the amino-terminus of Dsg1, a region critical for intercellular adhesion of cadherins, and this skewed amino-terminal immunoreactivity prevails across various activity stages in most patients, even upon remission. These findings are valuable for understanding the biology of Dsg-mediated cellular adhesion as well as for the development of epitope-based monitoring and therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
3
34
1
1
Order By: Relevance
“…Our results suggest that human autoimmunity conforms to the concept of ''original antigenic sin'', i.e., domination of the immune response by the initial epitope, which does not change over time. We recently also demonstrated that epitope spreading is rare in PF (Chan et al, 2010). Our results are in agreement with a previous study in which epitope shift rarely occurred in PV (Futei et al, 2000).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Our results suggest that human autoimmunity conforms to the concept of ''original antigenic sin'', i.e., domination of the immune response by the initial epitope, which does not change over time. We recently also demonstrated that epitope spreading is rare in PF (Chan et al, 2010). Our results are in agreement with a previous study in which epitope shift rarely occurred in PV (Futei et al, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…Li et al (2003) showed the possible intramolecular epitope spreading from EC5 at onset to EC1 and EC2 in active stage, and then toward EC5 in remission in endemic PF. As Chan et al (2010) suggested that epitope shift did not occur in nonendemic PF, the discrepancy may be due to the difference between endemic and nonendemic PF. Salato et al (2005) reported that intramolecular epitope spreading from EC2-5 to the EC1 domain of Dsg3 occurred and was a critical step for intermolecular epitope shift from Dsg3 to Dsg1.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Genetic and ethnic factors explain part of these observations [13], and other autoantibodies, such as anti-desmocollin or anti-acetylcholine receptor, are known to be involved in pemphigus pathophysiology [26,27]. Isolated cases of phenotypic and immunological transition from PV to PF or vice versa were described [28,29], but epitope spreading may not be implicated [30,31]. Furthermore, commercial Dsg ELISA kits detect only IgG autoantibodies, but IgA and IgE are known to be involved [27,32,33].…”
Section: Discussionmentioning
confidence: 99%